Contribution of advanced edge-detection methods of potential field data in the tectono-structural study of the southwestern part of Cameroon - Nzeuga, Alain Rodrigue; Ghomsi, Franck Eitel; Pham, Luan Thanh; Eldosouky, Ahmed M.; Aretouyap, Zakari; Kana, Janvier Domra; Yasmine, Zambou Tsopgni; Fokem, Alpha Baster Kenfack; Nouayou, Robert; Abdelrahman, Kamal; Fnais, Mohammed S.; Andráš, Peter (Frontiers in Earth Science, 2022)
The southwest part of Cameroon is composed of a range of geological structures and sedimentary basins, whose geological history dates from the Cretaceous, and their establishment would have originated from the opening of the South Atlantic. Among these structures, the most important is the Cameroon Volcanic Line, generally denoted CVL, followed by the southern part of the Central African Shear Zone (CASZ) called the Foumban Shear Zone (FSZ), the Ntem Complex, the Benue Trough, the northern margin of the Congo Craton, and many others. The major structures identified in this part are formed as a result of geodynamic activity between the Oligocene and the recent period, to which we can add the volcanism that exists along with the continental limit. The XGM201e_2159 model is used to highlight the geological structures of Southwestern Cameroon. First, we separated the regional and residual anomalies from Bouguer gravity data. Then, we used a combination of filters to enhance the signature of the residual anomalies in Southwest Cameroon. These filters identified various geological structures in the area. Finally, we applied the enhanced horizontal gradient amplitude (EHGA) and multi-scale horizontal derivative of the vertical derivative (MSHDVD) methods to reveal the geological contacts, allowing us to establish the corresponding structural map of the region. In addition, the results obtained in this study are the first to precisely define the circumferential demarcation of the continental and oceanic expansions of Mount Cameroon, while clearly illustrating the Bao, Bomana, Tiko, and Ekona faults that extend to the Bakassi Peninsula and the Douala outlet. Furthermore, they highlight the strike–slip faults in the summit vicinity. The structural map shows that most of the geological boundaries identified in the area are trending in the NE–SW, NNE–SSW, ENE–WSW, N–S, and NW–SE directions.